A clown in a grave : complexities and tensions in the works of Gregory Corso - Skau, Michael, 1944- (Southern Illinois University Press, 1999)
"Using a number of critical approaches, Michael Skau examines Gregory Corso's complex imagination, his humor, and his poetic techniques in dealing with America, the Beat generation, and death."--BOOK JACKET. "Skau covers the complete works of Corso, one of the four major Beat Generation writers (with Jack Kerouac, Allen Ginsberg, and William S. Burroughs) who attempted to provide an alternative to what they saw as the academic forms of literature dominating American writing through the 1940's and 1950's."--Jacket